Patient Factors and Hospital Outcomes Associated With Atypical Presentation in Hospitalized Older Adults With COVID-19 During the First Surge of the Pandemic. Issue 4 (19th July 2021) - Marziliano, Allison; Burns, Edith; Chauhan, Lakshpaul; Liu, Yan; Makhnevich, Alex; Zhang, Meng; Carney, Maria T; Dbeis, Yasser; Lindvall, Charlotta; Qiu, Michael; Diefenbach, Michael A; Sinvani, Liron
Abstract: Background: Literature indicates an atypical presentation of COVID-19 among older adults (OAs). Our purpose is to identify the frequency of atypical presentation and compare demographic and clinical factors, and short-term outcomes, between typical versus atypical presentations in OAs hospitalized with COVID-19 during the first surge of the pandemic. Methods: Data from the inpatient electronic health record were extracted for patients aged 65 and older, admitted to our health systems' hospitals with COVID-19 between March 1 and April 20, 2020. Presentation as reported by the OA or his/her representative is documented by the admitting professional and includes both symptoms and signs. Natural language processing was used to code the presence/absence of each symptom or sign. Typical presentation was defined as words indicating fever, cough, or shortness of breath; atypical presentation was defined as words indicating functional decline or altered mental status. Results: Of 4 961 unique OAs, atypical presentation characterized by functional decline or altered mental status was present in 24.9% and 11.3%, respectively. Atypical presentation was associated with older age, female gender, Black race, non-Hispanic ethnicity, higher comorbidity index, and the presence of dementia and diabetes mellitus. Those who presented typically were 1.39 times more likely than those who presented atypically to receive intensive care unit–level care. Hospital outcomes of mortality, length of stay, and 30-day readmission were similar between OAs with typical versus atypical presentations. Conclusion: Although atypical presentation in OAs is not associated with the same need for acute intervention as respiratory distress, it must not be dismissed.